Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.7150/jca.16525
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Albumin to Globulin Ratio (AGR) as Prognostic Factor in Renal Cell Carcinoma

Abstract: Background: Malnutrition and systemic inflammatory response are frequently associated with prognosis in patients with several types of cancer, including renal cell carcinoma (RCC). The study is aimed to investigate the ability of preoperative serum albumin to globulin ratio (AGR) to predict the long-term mortality of RCC patients.Methods: The study is a retrospective study of an unselected cohort of 895 RCC patients who underwent a curative radical or partial nephrectomy at the Department of Urology in the Sun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 29 publications
(30 reference statements)
0
32
0
Order By: Relevance
“…Several studies have regarded dNLR as an inflammation marker that can reflect the severity of systematic inflammation in several cancers, such as non–small cell lung cancer, colorectal cancer, and breast cancer . Serum albumin has been considered to have anti‐inflammatory and possible immunomodulatory properties; therefore, if albumin synthesis was restricted by systematic inflammation, damage to the immune defense system of the patient could occur . Moreover, previous studies have shown that serum albumin can reflect nutritional status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have regarded dNLR as an inflammation marker that can reflect the severity of systematic inflammation in several cancers, such as non–small cell lung cancer, colorectal cancer, and breast cancer . Serum albumin has been considered to have anti‐inflammatory and possible immunomodulatory properties; therefore, if albumin synthesis was restricted by systematic inflammation, damage to the immune defense system of the patient could occur . Moreover, previous studies have shown that serum albumin can reflect nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…13 Serum albumin has been considered to have anti-inflammatory and possible immunomodulatory properties 14 ; therefore, if albumin synthesis was restricted by systematic inflammation, damage to the immune defense system of the patient could occur. 15 Moreover, previous ALB-dNLR score, Albumin-dNLR score; CRP, C-reactive protein; DAS28 score, 28-joint count Disease Activity Score; DMARDs, disease-modifying anti-rheumatic drugs; dNLR (Derived neutrophil to lymphocyte ratio), Neutrophil count to (Leukocyte-Neutrophil count) ratio; ESR, Erythrocyte sedimentation rate; NSAIDs, non-steroidal anti-inflammatory drugs; RF, rheumatoid factor. Quantitative data are presented as median (IQR) or n (%), depending on the distribution.…”
Section: Discussionmentioning
confidence: 99%
“…The serum albumin concentration is a prognostic factor in many lung diseases (24,25). We did not follow up on the prognosis of our patients, but early studies have shown that the AGR can be utilized to evaluate tumor prognosis (26,27). The AGR was combined with two prognostic factors: the serum albumin and globulin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…With the systemic inflammation, ALB eliminates the nitrogen species and active oxygen, while it reduces in itself 23 , 24 . Many studies affirmed that ALB alone or based markers were correlated with survival in various cancers 23 , 25 - 27 . Similarly, ALB alone or based markers were confirmed as independent predictors of PDAC with poor survival 14 , 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%